Information literacy skills of secondary school students in Singapore - Oboho, Nse Eteyen (2008)
This thesis investigates the information literacy skills of secondary school students in Singapore. Yishun Secondary School and Raffles Girls' School were chosen for the purpose of the survey. An assessment of the students' level of skills in using different information sources, effectively aggregating and presenting information found for study related tasks, with an understanding of the ethical issues surrounding the use of information, was made.